CORRELATION BETWEEN HEMODIALYSIS FREQUENCY AND QUALITY OF LIFE OF CKD PATIENTS AT SAMARINDA MEDIKA CITRA HOSPITAL - Wina Mardiyah Pane (Universitas Negeri Surabaya, 2026)
Background: Chronic Kidney Disease (CKD) is a global health issue that significantly impacts patients' quality of life. In the end stage, patients require routine hemodialysis therapy. Irregularity in treatment frequency can lead to a decline in clinical condition and quality of life. Methods: This study employed a quantitative, descriptive-correlational design with a cross-sectional approach. A total of 43 respondents were selected using a total sampling technique from among CKD patients undergoing routine hemodialysis twice weekly at Samarinda Medika Citra Hospital. The instruments used were a hemodialysis frequency observation sheet and the Kidney Disease Quality of Life-36 (KDQOL-36) questionnaire. Data analysis was performed using the Spearman Rank test. Results: The study results showed a mean hemodialysis frequency of 23.6 and a mean quality of life score of 63.35. A significant correlation was found between hemodialysis frequency and quality of life (p=0.002; r=0.459), characterized by a moderate, positive correlation. Conclusion and Recommendations: There is a significant correlation between hemodialysis frequency and the quality of life of CKD patients. Adherence to the hemodialysis schedule plays a crucial role in improving patients' quality of life. Healthcare professionals are advised to enhance patient education and the monitoring of treatment adherence.